Visitor Perceptions of the Implementation of GeoBeat Ecotopia as an Implementation of Sustainable Events at Geo Open Space, Kerobokan Kelod - Cahyani, Stefani Rosa Kurnia; Paramita, Ratri; Asmarani, I G A Ratih (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The surge in domestic and foreign tourists to the island of Bali has had both positive and negative impacts. Many tourists come to visit Bali for necessities, leisure or attend an event/event, but many do not apply sustainable principles, producing waste and environmental damage. This research evaluates GeoBeat Ecotopia as an example of a sustainable event. This research method is quantitative descriptive using Silvers' 6-dimensional theory (anticipation, arrival, atmosphere, appetite, activity, amenities) and a Likert scale for 80 respondents from a total population of 409 visitors with techniques of probability sampling approach sample random sampling. The types of data used are quantitative and qualitative data. This research uses data collection techniques from observation, distribution of questionnaires, interviews and documentation studies. Quantitative data is processed using software SPSS. The results of this research are visitors' perceptions of GeoBeat Ecotopia as an implementation sustainable event overall very good (average 4.66) by score order activity (4,76), atmosphere (4,75), arrival (4,71), anticipation (4,59), amenities (4,65), appetite (4.51). The dimension with the highest average score is dimension activity while the dimension with the lowest average score is dimension appetite.